Digital diversification to expand the Indonesian radio industry: A Case Study of PRFM, Delta, and Dahlia Stations - Septiawan Santana Kurnia; Firmansyah; Dadi Ahmadi; Doddy Iskandar Cakranegara; Satya Indra Karsa; Erwin Kustiman (Penerbit Universiti Kebangsaan Malaysia, 2023)
Digitization has made radio stations the business of news portals, global aggregator platforms, programmed journalism or algorithm journalism. How does the radio broadcasting business retain an audience and grow listeners across borders via Facebook, Twitter, Instagram, Youtube, TikTok, WhatsApp and Website? How does the radio broadcasting business disseminate information and promotions more intimately, personally and widely? How the radio broadcasting business is accessible to audiences, fun and mobile: pocketable, openable on mobile phones, computers, iPads and more? How do listeners interact and communicate anytime and anywhere? The answer is digitalization that has changed radio technology, social culture, economy and generations. These changes affect the management, production, distribution, and reception of radio broadcast listeners. The governance of the radio broadcasting business has been mandated, commissioned, and inspired by a unique public service. This research uses a "Case Study", and Single Multi-Level Case Analysis, to confirm the theoretical proposition, of digitalization technology, in practice communication technology, which is used to develop radio broadcasting governance. How is the digitization of radio broadcasting governance used as an information technology tool, as a tool for developing marketing, and as a tool for information business diversification? Qualitative data were coded from observations, open interviews, Focus Group Discussions, and detailed documents to assess the views and experience of digitizing radio broadcast managers in managerial and business development.